Vitamin D Levels Are Associated With Pain and Pain Catastrophizing in Patients With Fibromyalgia Syndrome - Yentuer, Songuel Baglan; Elbasti, Muhammed Sahin (Erciyes Univ Sch Medicine, 2024)
Objective: Low vitamin D (VD) levels may increase pain sensitivity, particularly by enhancing central sensitivity. Fibromyalgia is associated with disruptions in neurotransmitters and inflammatory pathways within the central nervous system, leading to an increased sensitivity of pain signals. This study aimed to investigate the relationship between vitamin D levels and pain, pain catastrophizing, function, depression, and anxiety. Materials and Methods: This study included 153 patients with Fibromyalgia Syndrome (FMS) and 153 healthy individuals. Vitamin D levels were measured using 5 ml blood samples obtained from both patients and healthy individuals. The Hospital Anxiety and Depression Scale (HADS), Pain Catastrophizing Scale (PCS), McGill Pain Questionnaire-Short Form (MPQ), and Fibromyalgia Impact Questionnaire (FIQ) were used to evaluate pain, pain catastrophizing, psychological symptoms, and function, respectively. Results: VD levels were statistically lower in the FMS group (17.71 +/- 9.32 ng/ml) compared to the control group (20.40 +/- 9.33 ng/ml) (p<0.05). No statistical difference was found among groups classified according to vitamin D subgroups in terms of FIQ, MPQ, PCS, and HADS scores (p>0.05). There was a negative correlation between VD levels and MPQ, as well as all subgroups of PCS (p>0.05), while no significant correlation was found between VD levels and depression, anxiety, or function. Conclusion: VD levels in patients with FMS were found to be lower than those in healthy individuals, and VD levels were associated with pain and pain catastrophizing in this study. Physician-supervised VD supplementation may improve pain catastrophizing in patients with FMS.
Keywords: Fibromyalgia; pain; pain catastrophizing; vitamin D